(untitled) (Journal of Educational Sciences, 2016)
In the article the red thread runs through the idea that the musical-aesthetic education should be an integralpart of the activities conducted by the teachers of the formation of a harmoniously developed person. The author believes that learning and critical reflection foreign pedagogical experience will help to develop the scientifically substantiated conclusions for theory and practice of the national system of education. The article compares the system of higher musical education in the leading countries of Europe, with its own traditions and history of music education. On the basis of the developed in the musical-pedagogical science of various approaches to the study of the history of music education the author uses a new conceptual level of the research of the process of formation and development of musical education in Germany and England. Discussed in the article the system of musical education In Germany is focused on the globalization processes taking place in education, studied авторм their national specifics of the educational process sacrificed in international priorities, i.e. the possibility of relying on the same criteria for education. The author analyzed compulsory subjects in obtaining the musical-pedagogical education. The article revealed that academic disciplines, which are taught in the schools of England has some resemblance to the disciplines that are taught in the Kazakh musical educational institutions (playing the percussion instruments, music, performing arts, performing arts, arrangement, sound recorder, music theory, keyboard, ensemble, the history of the modern music of the 20th century, music management, modern and classical music, the setting of voice, singing lessons, the technique of playing the guitar, bass guitar). It is proved that for all the specific characteristics of musical education of the individual countries they reflect actual and common to all approaches to the content, forms and methods of teaching music. In these countries a special musical education was and is elitist, in higher education institutions shall apply the creative exam, increased role of independent work of students on the basis of the recognition of diverse destination of musical education there are new specializations, conditions are created for activation of creative activity of students, developing democratic processes in the sphere of management of musical educational institutions.